PENINGKATAN KREATIVITAS SISWA MELALUI METODE PROJECT BASED LEARNING DALAM PEMBELAJARAN SENI BUDAYA KELAS VIII.3 DI SMP NEGERI 6 SINGARAJA - Gusti Ayu Rani Hitayanti; I Nyoman Sila; Luh Suartini (Jurnal Pendidikan Seni Rupa Undiksha, 2026)
This study aimed to enhance students’ creativity through the implementation of Project Based Learning in Cultural Arts learning, particularly visual arts, at SMP Negeri 6 Singaraja. The background of this research was based on the low level of student creativity, which was reflected in poster works that appeared monotonous, less varied, and highly dependent on examples from the internet. This research employed a qualitative approach using Classroom Action Research conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were students of class VIII.3 who experienced difficulties in developing ideas independently. The results showed a significant improvement in students’ creativity from the first cycle to the second cycle. Students were able to produce more varied, original, and aesthetically improved artworks. In addition, students’ self-confidence increased and the tendency to imitate decreased. The learning process became more active, well-managed, and student-centred. Therefore, Project Based Learning proved to be effective in improving students’ creativity. This study implies that innovative teaching methods are essential to create meaningful learning experiences and to optimise students’ potential. Keywords: creativity, Project Based Learning, visual art